A case of Finegoldia magna (formerly Peptostreptococcus magnus) infection mimicking disseminated malignancy. (December 2016) - Basu, Pallavi; Williams, Anwen; O'Brien, Matthew T.; Brouns, Mattheus; Edwards, Paul
Highlights: A case of Finegoldia magna infection is reported; F. magna is a Gram-positive anaerobic coccus. In this case, the F. magna infection mimicked malignancy on computed tomography scanning. The F. magna infection presented as systemic inflammation and multiple visceral and cutaneous lesions. Immunosuppression and malnutrition promote infection by commensal bacteria. Tissue diagnosis is important in suspected malignancy. Summary: A 44-year-old alcoholic (and therefore immunocompromised) hospital cleaner presented with general malaise, weight loss, and erythematous skin nodules. Computed tomography scanning revealed a neck mass invading the thyroid gland, pulmonary infiltrates, liver lesions, and deposits on the anterior abdominal wall, consistent with disseminated malignancy. However, tissue diagnosis showed a necro-inflammatory process with no evidence of malignancy. Microscopy and culture of samples failed to detect any infectious pathogen, but after an extended incubation period, Finegoldia magna was isolated. This case study illustrates the importance of tissue diagnosis in suspected disseminated malignancy and raises the risk of acquiring the rarer bacteria amongst hospital staff.